Anti-inflammatory effects of soyasapogenol I-αa via downregulation of the MAPK signaling pathway in LPS-induced RAW 264.7 macrophages. (March 2018) - Yang, Seung Hwan; Le, Bao; Androutsopoulos, Vasilis P.; Tsukamoto, Chigen; Shin, Tae-Sun; Tsatsakis, Aristides M.; Chung, Gyuhwa
Abstract: The crude extract of soyasaponins was reported to possess anti-inflammatory activity. We determined the new purity group I saponin, I-αa and I-γa that was isolated from wild soybean ( Glycine soja ) in terms of its efficacy in protecting RAW 264.7 macrophages from lipopolysaccharide (LPS)-stimuli. Cells were treated with soyasaponin I-αa/I-γa (30–300 μΜ) and LPS (0.1 μg/mL) for 24 h. Soyasaponin I-αa inhibited nitric oxide (NO) production at 100 μg/mL, while soyasaponin I-γa demonstrated this effect at a higher concentration (200 μg/mL). The expression levels of iNOS and COX-2 enzymes were downregulated by both soyasaponins. Soyasaponin I-αa exerted its effect via the TNF-α and IL-1β cytokines. However, soyasaponin I-γa only inhibited the expression of TNF-α. The inflammatory effect of group I soyasaponin was mainly mediated via the phosphorylation of the p38 and JNK proteins. Collectively, these results suggested the potential anti-inflammatory effects of soyasaponins. Graphical abstract: Highlights: Anti-inflammatory effects of a group I saponins from Glycine soja are reported. Soyasaponin I-αa inhibited the TNF-α and IL-1β cytokine induced NO generation in RAW 264.7 macrophages. Soyasaponin I-γa only inhibited the expression of TNF-α. Group I soyasaponin stimulated anti-inflammatory effects via mechanisms related to the p38 and JNK signaling pathways.